Designing and Engineering Methylorubrum extorquens AM1 for Itaconic Acid Production - Lim, Chee Kent; Villada, Juan C.; Chalifour, Annie; Duran, Maria F.; Lu, Hongyuan; Lee, Patrick K. H. (Frontiers in Microbiology, 2019)
Methylorubrum extorquens (formerly Methylobacterium extorquens) AM1 is a methylotrophic bacterium with a versatile lifestyle. Various carbon sources including acetate and methanol are utilized by M. extorquens AM1 with the latter being a promising inexpensive substrate for use in the biotechnology industry. Itaconic acid is a high-value building block widely used in various industries. Given that no wildtype methylotrophic bacteria are able to utilize methanol to produce itaconic acid, we tested the potential of M. extorquens AM1 as an engineered host for this purpose. In this study, we successfully engineered M. extorquens AM1 to express a heterologous codon-optimized gene encoding cis-aconitic acid decarboxylase. The engineered strain produced itaconic acid using acetate and methanol as the carbon feedstock. The highest itaconic acid titer in batch culture with methanol as the carbon source was 31.6 ± 5.5 mg/L, while the titer and productivity were 5.4 ± 0.2 mg/L and 0.056 ± 0.002 mg/L/h respectively in a scaled-up fed-batch bioreactor under 60% dissolved oxygen saturation. We attempted to enhance the carbon flux towards itaconic acid production by impeding poly--hydroxybutyrate accumulation, which is used as carbon and energy storage, via mutation of the regulator gene phaR. Unexpectedly, itaconic acid production by the phaR mutant strain was not higher even though poly--hydroxybutyrate concentration was lower. Genome-wide transcriptomic analysis revealed that phaR mutation in the itaconic acid-producing strain led to complex rewiring of gene transcription, which might result in a reduced carbon flux towards itaconic acid production. Besides poly--hydroxybutyrate metabolism, we found evidence that PhaR might regulate the transcription of many other genes including those encoding other regulatory proteins, methanol dehydrogenases and formate dehydrogenases in carbon metabolism, membrane-associated malate:quinone oxidoreductase in the tricarboxylic acid cycle, and those synthesizing pyrroloquinoline quinone and thiamine co-factors. Overall, M. extorquens AM1 was successfully engineered to produce itaconic acid using methanol and acetate as feedstock, further supporting this bacterium as a feasible host for use in the biotechnology industry. This study showed that PhaR could have a broader regulatory role than previously anticipated, and increased our knowledge of this regulator and its influence on the physiology of M. extorquens AM1.